2014
DOI: 10.5935/1678-9741.20140092
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Bypass Increases the Risk of Vasoplegic Syndrome After Coronary Artery Bypass Grafting in Patients With Dialysis-Dependent Chronic Renal Failure

Abstract: ObjectiveCoronary artery bypass grafting is currently the best treatment for dialysis patients with multivessel coronary artery involvement. Vasoplegic syndrome of inflammatory etiology constitutes an important postoperative complication, with highly negative impact on prognosis. Considering that these patients have an intrinsic inflammatory response exacerbation, our goal was to evaluate the incidence and mortality of vasoplegic syndrome after myocardial revascularization in this group.MethodsA retrospective,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 24 publications
(44 reference statements)
1
14
0
1
Order By: Relevance
“…The use of CPB in cardiac surgery has been frequently linked with vasoplegia, with the rate of vasoplegia being higher for patients who have CPB than for those who have offpump coronary artery bypass surgery. 9 Our study also reflected this inflammatory cascade, with worsening vasoplegia as CPB duration increased. The rates of concomitant procedures also increased across the vasoplegia severities, which may partly explain the increased CPB durations.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The use of CPB in cardiac surgery has been frequently linked with vasoplegia, with the rate of vasoplegia being higher for patients who have CPB than for those who have offpump coronary artery bypass surgery. 9 Our study also reflected this inflammatory cascade, with worsening vasoplegia as CPB duration increased. The rates of concomitant procedures also increased across the vasoplegia severities, which may partly explain the increased CPB durations.…”
Section: Discussionsupporting
confidence: 64%
“…7 Another study reported a mortality rate of 50% for dialysis-dependent patients who underwent CPB and subsequently developed vasoplegia. 9 Our work reiterated the association between vasoplegia and mortality, as patients with moderate to severe vasoplegia had a >2-fold increase in risk of mortality. In addition, we observed higher rates of major bleeding episodes among vasoplegic patients.…”
Section: Discussionmentioning
confidence: 63%
“…Evidências mostram que a diminuição da resposta inflamatória na CRM sem CEC leva a uma redução de disfunção orgânica, 2 assim como menores índices de vasoplegia e lesão renal. 12 Neste cenário, análises retrospectivas em grandes populações confirmam uma redução significativa da morbimortalidade quando a CRM é realizada sem CEC. 13,14 Assim, mesmo uma análise nos quatro maiores centros dos EUA mostrou benefício quando a CRM foi realizada sem CEC, principalmente nos pacientes considerados de alto risco.…”
Section: Discussionunclassified
“…22 Vasoplegia can occur during CPB because of the activation of nitric oxide synthase, smooth muscle K+ channels, and relatively reduced vasopressin levels. 23 It results in systemic vasodilation and hypotension that is resistant to conventional therapy. Methylene blue, a competitive inhibitor of nitric oxide, can be used as a rescue drug.…”
Section: Mechanical Complications Of Cardiopulmonary Bypassmentioning
confidence: 99%
“…Methylene blue, a competitive inhibitor of nitric oxide, can be used as a rescue drug. 23 Hemolysis occurs in all extra-corporeal circuits due to shear stress, wall impact forces, contact with non-endothelial surfaces, positive and negative pressures. A high degree of hemolysis that goes beyond the endogenous clearing mechanisms can lead to the accumulation of plasma-free Hb.…”
Section: Mechanical Complications Of Cardiopulmonary Bypassmentioning
confidence: 99%